Organizational support for the workforce and employee safety citizenship behaviors: A social exchange relationship. (March 2017) - Reader, Tom W; Mearns, Kathryn; Lopes, Claudia; Kuha, Jouni
Employee safety citizenship behaviors are crucial to risk management in safety-critical industries, and identifying ways to encourage them is a priority. This study examines (i) whether safety citizenship behaviors are a product of social exchanges between employees and organizations, and (ii) the organizational exchanges (i.e. actual activities to support employees) that underlie this relationship. We studied this in the offshore oil and gas industry, and investigated whether organizational activities for supporting workforce health are a signal to employees that the organization supports them, and an antecedent to safety citizenship behaviors. Using questionnaires, we collected data from employees ( n = 820) and medics ( n = 30) on 22 offshore installations. Multi-level path analysis found that where activities to support workforce health were greater, offshore employees were more likely to perceive their organization to support them, and in turn report more commitment to the organization and safety citizenship behaviors. This indicates safety citizenship behaviors are a product of social exchange, and provides insight on how organizations can influence employee engagement in them. It also suggests social exchange theory as a useful framework for investigating how organizational safety is influenced by workforce relations. We contributed to the social exchange literature through conceptualizing and demonstrating how organizational exchanges lead to reciprocal employee citizenship behaviors.